The Effect of Concentration of Ecoenzyme on Growth of Mustard Plants (Brassica juncea L.) - Surya Tati; Azwir Anhar (Jurnal Serambi Biologi, 2022)
Mustard (Brassica juncea L.) is an annual plant containing 22.0 calories of calories and also contains vitamins such as protein, calcium, phosphorus, vitamin A, vitamin B, vitamin C. So far, the source of nutrients for plant needs is met with synthetic fertilizers. The use of these in the long term is not beneficial for the environment, so efforts are needed to replace the use of synthetic with organic fertilizers. One product that has the potential to become liquid organic fertilizer is ecoenzyme. This aims to determine the growth response of mustard to the administration of ecoenzyme concentrations. This is an experimental study using a Completely Randomized Design (CRD) consisting of 7 treatments and 4 replications. The treatments given were water and Liquid Organic Fertilizer (POC) as control and 0.5%, 1%, 1.5%, 2%, and 2.5% ecoenzymes. Parameters were plant height, leaf cover, wet weight, and plant dry weight. The obtained were analyzed by means of ANOVA (Analysis of Variance) and Duncan's Multiple Range Test (DMRT) further test. The results showed the administration of various concentrations of ecoenzymes did not significantly of mustard greens, plant height, leaf area, wet weight, and dry weight. Key words: Mustard (Brassica juncea L.), growth, concentration, ecoenzyme